ELECTIC THEORY AND PRACTICE OF ATTRACTING FOREIGN DIRECT INVESTMENT INTO NGHE AN PROVINCE - Tran Thi Hoang Mai*, Nguyen Huu Truong (Tạp chí Khoa học)
In recent years, Nghe An has made a miracle in attracting foreign direct investment, when it is continuously in the top 10 localities leading in foreign direct investment attraction nationwide. The study approaches from the eclectic theory perspective to explain the province's success in creating advantages ready to receive foreign enterprises to the locality. The research results show that Nghe An has prepared the factors to create location advantages, especially the readiness in planning, connecting infrastructure and clean land, and determination to reform administrative procedures. However, factors still need to be improved soon to create advantages in ownership and internalization. The study also proposes several solutions to increase the attraction of this capital source in the coming time.